2005
DOI: 10.1093/ejo/cjh085
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion of two lingual retainer adhesives cured with different light sources

Abstract: The aim of this study was to evaluate the degree of conversion (DC) of two lingual retainer adhesives, Transbond Lingual Retainer (TLR) and Light Cure Retainer (LCR), cured with a fast halogen light, a plasma arc light and a light-emitting diode (LED) at various curing times. A conventional halogen light served as the control. One hundred adhesive samples (five per group) were cured for 5, 10 or 15 seconds with an Optilux 501 (fast halogen light), for 3, 6 or 9 seconds with a Power Pac (plasma arc light), or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…On the effect exerted by the type of composite used on DC, it is noteworthy that the two composite materials tested in this study differed in numerous aspects: viscosity, chemical structure of the dimethacrylate monomer, translucency, photoinitiator concentration, and color tone (shade). Consequently, the results obtained in this study reflected these differences 2,16,24) . It has also been reported that monomers such as 2,2-bis[4-(2-hydroxy-3 methacryloxypropoxy)phenyl]propane (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) reached 85-90% of their final DC in 40 seconds with a QTH light unit 13) .…”
Section: Effect On the DC Of Lingual Retainer Compositessupporting
confidence: 73%
See 4 more Smart Citations
“…On the effect exerted by the type of composite used on DC, it is noteworthy that the two composite materials tested in this study differed in numerous aspects: viscosity, chemical structure of the dimethacrylate monomer, translucency, photoinitiator concentration, and color tone (shade). Consequently, the results obtained in this study reflected these differences 2,16,24) . It has also been reported that monomers such as 2,2-bis[4-(2-hydroxy-3 methacryloxypropoxy)phenyl]propane (Bis-GMA) and triethylene glycol dimethacrylate (TEGDMA) reached 85-90% of their final DC in 40 seconds with a QTH light unit 13) .…”
Section: Effect On the DC Of Lingual Retainer Compositessupporting
confidence: 73%
“…The DC values determined by Üşümez 2) et al for TLR and LCR were 55.5±10.3% and 67.6±5.7% respectively. In the present study, statistical evaluation of the pooled overall DC data of the same two composites yielded 68.38±9.31% for TLR and 84.37±3.54% for LCR.…”
Section: Effect On the DC Of Lingual Retainer Compositesmentioning
confidence: 83%
See 3 more Smart Citations